NEW DATA ON GAS COMPOSITION OF THE AIR IN GYPSUM CAVES FROM PODILLYA AND BUKOVYNA - Bondar, K.; Sachko, A.; Churubrov, M.; Mamyshev, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The paper presents new results of the study of the air gas composition (AGC) of the Podillya caves (Atlantida, Optymistychna, Mlynky) and Bukovina (Popelyushka) by the chromatographic method. The AGC comparison is made on the basis of air samples taken during the winter period. The previously known features of AGCof caves are confirmed. In particular, it has been shown that cave air contains an increased amount of CO2 comparing to atmospheric air. The highest concentrations of CO2 were registered in Popelyushka (4.10 vol. %), and the lowest – in Optimistic cave (0.12 vol. %). In addition, there is an oxygen depletion of cave air away from the sides of the gypsum block registered in the Optymistychna cave. Helium and hydrogen are also found in this cave in significant concentrations, which allows considing deep breakdowns within the cave field. The long-term stability of the AGC of the Popelyushka cave is established and the absence of methane in the cave air is shown. Changes in AGC of caves, associated with anthropogenic load, are detected. In particular, in the Atlantida cave, the air pollution with hydrocarbons is proved.